2019
DOI: 10.1039/c9ee02043h
|View full text |Cite
|
Sign up to set email alerts
|

I2 vapor-induced degradation of formamidinium lead iodide based perovskite solar cells under heat–light soaking conditions

Abstract: We reveal an iodine vapor-induced degradation mechanism in formamidinium–lead-iodide-based perovskite solar cells stressed under combined heat and light illumination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
211
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(215 citation statements)
references
References 88 publications
(116 reference statements)
4
211
0
Order By: Relevance
“…[111] Another thermal-and light-induced degradation mechanism is the release of I 2 . [112] ToF-SIMS results showed that the PbI 2 concentration decreases in PbI 2 film during heating-light soaking at 80 °C under solar cell operational condition, suggesting that PbI 2 decomposes to Pb and I 2 . [112] In perovskite film, the PbI 2 concentration increases but the MA concentration decreases after the heating-light soaking test.…”
Section: Light and Temperature Effectsmentioning
confidence: 98%
See 1 more Smart Citation
“…[111] Another thermal-and light-induced degradation mechanism is the release of I 2 . [112] ToF-SIMS results showed that the PbI 2 concentration decreases in PbI 2 film during heating-light soaking at 80 °C under solar cell operational condition, suggesting that PbI 2 decomposes to Pb and I 2 . [112] In perovskite film, the PbI 2 concentration increases but the MA concentration decreases after the heating-light soaking test.…”
Section: Light and Temperature Effectsmentioning
confidence: 98%
“…[112] ToF-SIMS results showed that the PbI 2 concentration decreases in PbI 2 film during heating-light soaking at 80 °C under solar cell operational condition, suggesting that PbI 2 decomposes to Pb and I 2 . [112] In perovskite film, the PbI 2 concentration increases but the MA concentration decreases after the heating-light soaking test. Therefore, combining with other investigations, it was suggested that the loss of MA under heating-light soaking triggers the release of I 2 vapor, which deteriorates neighboring perovskite and further leads to the decomposition of perovskite.…”
Section: Light and Temperature Effectsmentioning
confidence: 98%
“…However, the progress in improving the stability of PSCs is far from being satisfactory, and therefore, short operation lifetimes represent the main obstacle for successful commercialization of perovskite photovoltaic technology . Complex lead halides with a perovskite crystal structure were shown to be very sensitive substances readily decomposing under exposure to moisture (hydrolysis), oxygen, and light (photooxidation), and reactive chemical vapors such as iodine . While these extrinsic degradation pathways can be mitigated by encapsulation of perovskite films and their isolation from aggressive environment, a particular concern is raised about intrinsic stability of complex lead halides, because they can decompose at elevated temperatures and under light exposure even in inert atmosphere .…”
Section: Introductionmentioning
confidence: 99%
“…Stable PSCs under 85 • C and one sun illumination for 1000 h have not been reported yet, though promising results for 500 h have been demonstrated [35,36]. Moreover, under constant light and heat, PSCs perform worse if analysed under open circuit voltage conditions than under the MPP tracking mode, indicating that ion migration and charge accumulation are critical for the stability of PSCs [37,38]. Therefore, the long-term stability of PSCs analysed under the combination of light, elevated temperature and bias voltage is significantly important and can be considered as a prerequisite towards commercialization.…”
Section: Combination Of Stress Factorsmentioning
confidence: 99%
“…Therefore, the long-term stability of PSCs analysed under the combination of light, elevated temperature and bias voltage is significantly important and can be considered as a prerequisite towards commercialization. An important challenge originates from I 2 -induced degradation [38,39], thermal decomposition, ion migration, interface deterioration and their coupling with defects, leading to accelerated degradation processes. Particularly, the generation of I 2 vapour, which originates from either the oxidation of Iby photo-generated holes [40] or decomposition of the halide perovskite through the presence of defects in the bulk, is a self-catalysed reaction, and thus urgent innovative solutions are necessary to address this problem [38].…”
Section: Combination Of Stress Factorsmentioning
confidence: 99%